Reimagining public sector management : a new age of renewal and renaissance? - Diamond, John; Liddle, Joyce (Emerald Publishing Limited, 2022)
In this latest volume of the Critical Perspectives on International Public Sector Management series, Professors John Diamond and Joyce Liddle have gathered leading scholars and new research to help discern some immediate areas of public policy making that have been impacted by the Covid-19 pandemic. With this new profoundly different context, "business as normal" is seen as no longer viable. Reimagining Public Sector Management delves into the crisis and emergency management of the pandemic, exploring the ways in which different agencies responded to the pandemic and the lessons learnt in terms of disaster planning and co-ordination. Chapters analyse the ways in which health services and the associated work linked to vaccine development provided significant lessons for those involved in public policy making and analysis before highlighting the emergence of a new consensus on the role of public agencies and institutions could play in the post pandemic environment as captured in the slogan "Build Back Better".
Keywords: Public administration -- Management.; Political Science -- Public Affairs & Administration.; Public administration.; elektronické knihy; electronic books